2020
DOI: 10.1103/physrevresearch.2.013197
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dimension reduction in phenotypic space

Abstract: In general, cellular phenotypes, as measured by concentrations of cellular components, involve large degrees of freedom. However, recent measurement has demonstrated that phenotypic changes resulting from adaptation and evolution in response to environmental changes are effectively restricted to a low-dimensional subspace. Thus, uncovering the origin and nature of such a drastic dimension reduction is crucial to understanding the general characteristics of biological adaptation and evolution. Herein, we first … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Experimental studies also suggest that both amplitude and correlation of phenotypic noise on multiple characters are evolvable (Stewart-Ornstein et al 2012;Yvert et al 2013). Moreover, the ability of the genotype-to-phenotype map to shape the random distribution of phenotypes, independently from the genetic variability, has been recently suggested by Sato and Kaneko (2019) and Sakata and Kaneko (2020). They have shown with analytical and numerical approaches that due to the evolution of the genotype-to-phenotype map, the distribution of phenotypes in a population can be restricted to a subspace as a result of evolution in variables environments.…”
Section: Discussionmentioning
confidence: 98%
“…Experimental studies also suggest that both amplitude and correlation of phenotypic noise on multiple characters are evolvable (Stewart-Ornstein et al 2012;Yvert et al 2013). Moreover, the ability of the genotype-to-phenotype map to shape the random distribution of phenotypes, independently from the genetic variability, has been recently suggested by Sato and Kaneko (2019) and Sakata and Kaneko (2020). They have shown with analytical and numerical approaches that due to the evolution of the genotype-to-phenotype map, the distribution of phenotypes in a population can be restricted to a subspace as a result of evolution in variables environments.…”
Section: Discussionmentioning
confidence: 98%
“…Larger conformational changes are governed by low-dimensional slow modes. Recent reports have shown that the dimensions of biologically relevant modes are reduced through evolution [67,68]. Such evolutionary dimensional reduction was also observed in the phenotypic dynamics of proteins [28,29,69].…”
Section: Discussionmentioning
confidence: 70%
“…Larger conformational changes are governed by low-dimensional slow modes. Recent reports have shown that the dimensions of biologically relevant modes are reduced through evolution [66,67]. Such evolutionary dimensional reduction was also observed in the phenotypic dynamics of proteins [28,29,68].…”
Section: Discussionmentioning
confidence: 70%